2017
DOI: 10.3892/etm.2017.4593
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-375 targets PAX6 and inhibits the viability, migration and invasion of human breast cancer MCF-7 cells

Abstract: Abstract. MicroRNAs (miRs) are a type of small non-coding RNA that serve crucial roles in the development and progression of breast cancer. However, the exact role and underlying molecular mechanism of miR-375 in mediating the growth and metastasis of breast cancer remains unknown. In the present study, reverse transcription-quantitative polymerase chain reaction and western blot analysis were conducted to examine RNA and protein expression. A luciferase reporter assay was performed to determine the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Interestingly, other studies have shown that increased expression of miR-34a and miR-375 reduces cell viability of cancer cell lines. 57,58 In this regard, our present data also showed that BAY 11-7082 decreases the levels of "oncomirs", miR-155, miR-192 and miR-21 levels, while increasing the levels of "tumour suppressors", miR-34a and miR-375, raising the view that specific cancer-related miRNAs interactions may be at least partially responsible for decreased cells viability. and -451a in treated hypopharyngeal mucosa.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, other studies have shown that increased expression of miR-34a and miR-375 reduces cell viability of cancer cell lines. 57,58 In this regard, our present data also showed that BAY 11-7082 decreases the levels of "oncomirs", miR-155, miR-192 and miR-21 levels, while increasing the levels of "tumour suppressors", miR-34a and miR-375, raising the view that specific cancer-related miRNAs interactions may be at least partially responsible for decreased cells viability. and -451a in treated hypopharyngeal mucosa.…”
Section: Discussionsupporting
confidence: 74%
“…The preferential effect of BAY 11‐7082 in acidic bile‐treated groups is especially interesting because it suggests its effect on cell viability is not global but related to specific events, in those groups. Interestingly, other studies have shown that increased expression of miR‐34a and miR‐375 reduces cell viability of cancer cell lines 57, 58. In this regard, our present data also showed that BAY 11‐7082 decreases the levels of “oncomirs”, miR‐155, miR‐192 and miR‐21 levels, while increasing the levels of “tumour suppressors”, miR‐34a and miR‐375, raising the view that specific cancer‐related miRNAs interactions may be at least partially responsible for decreased cells viability.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, upregulation of PAX6 attenuated the inhibitory effect of miR-758 in CRC. In consistency with the results of the present study, PAX6 has also been reported to be upregulated in retinoblastoma and breast cancer (25,26). In particular, as a target of miR-7, PAX6 was found to promote proliferation and invasion of CRC cells (27).…”
Section: Discussionsupporting
confidence: 92%
“…miRNA-320b is down-regulated in various cancers, and it is associated with tumorigenesis and poor prognosis in glioma. 42 miRNA-375 was also shown to be often down-regulated in NSCLC, 43,44 breast cancer, 45 colorectal cancer, [46][47][48][49] oesophageal cancer, 50,51 gastric cancer, 52,53 and pancreatic cancer. 54,55 It is associated with tumour proliferation and metastases.…”
Section: Discussionmentioning
confidence: 99%